Primary tuberculous gingival enlargement - A rare clinical entity: Case report and brief review of the literature - Suhail Majid Jan; Fayiza Youqoob Khan; Muzafar Ahmad Bhat; Roobal Behal (Wolters Kluwer Medknow Publications, 2014)
Tuberculosis (TB) is a chronic specific granulomatous disease and a major cause of death in developing countries. The clinical presentation of TB lesions of the oral cavity varies widely and can manifest as ulcerations, diffuse inflammatory lesions, granulomas and fissures. Oral lesions generally appear secondary to primary TB infection elsewhere, although primary infection of the oral mucosa by Mycobacterium tuberculosis has also been described. We hereby report a case of primary TB of the gingiva manifesting as gingival enlargement. Diagnosis was based on histopathological examination, complete blood count, X-ray chest and immunological investigations with detection of antibodies against M. tuberculosis. Anti-tuberculous therapy was carried out for over 6 months and was followed by surgical excision of the residual enlargement under local anesthesia. After 1-year follow-up, there was no recurrence of the disease. This case report emphasizes the need for dentists to include TB in the differential diagnosis of various types of gingival enlargements.